Pengaruh Fasilitas Toko, Harga dan Variasi Produk Terhadap Keputusan Pembelian Pada Warkop Medan Di Jakarta Cabang Galaxy Kota Bekasi - Aulia Ambarwati; Dhian Tyas Untari; Andrian Andrian (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the influence of store facilities, prices and product variations on purchasing decisions at warkop medan in Jakarta, galaxy branch, Bekasi City. This study is a quantitative research that uses primary data through questionnaires that are distributed directly or using QR codes to each consumer of Warkop Medan in Jakarta, Galaxy Branch, Bekasi City. The number of questionnaires distributed was 105 Based on the results of the partial test, it was proved that the store facility was rejected which means there was no meaningful relationship between the Store Facility and the Purchase Decision, the Price variable showed that the Price had an effect on the Purchase Decision. In the variable Product Variation, which means that there is no meaningful relationship between Product Variation and Purchase Decisions. However, this study proves that Store Facilities, Prices and Product Variations have a positive effect which means that simultaneously there is an influence on purchase decisions.